Modeling and control of a small hydro-power plant for a DC microgrid (2020)
This paper presents the modeling and control of a small hydro-power plant (SHP) for a DC microgrid based on passivity theory. The SHP is made up of a turbine, a permanent magnet synchronous generator (PMSG), a voltage source converter and a DC microgrid. The electrical, mechanical and hydraulic dynamics in the mathematical model of the SHP are considered. We employ a nonlinear controller based on passivity, whose stability is guaranteed under practically reasonable assumptions. Our simulation results show better performance of the proposed controller when compared with a PI controller in all of the scenarios that were considered. © 2019 Elsevier B.V.